Improved electrochemical performance of tin-sulfide anodes for sodium-ion batteries1. Issue 33 (7th September 2015) - Lu, Ying Ching; Ma, Chuze; Alvarado, Judith; Dimov, Nikolay; Meng, Ying Shirley; Okada, Shigeto
<x xml:space="preserve">Abstract</x> Due to their highly reversible capacity, tin-sulfide-based materials have gained attention as potential anodes for sodium-ion and lithium-ion batteries.